The ecological and the existential: sound and subjectivity in the works of Salvatore Sciarrino and Helmut Lachenmann - Li, M (2023)
This thesis demonstrates the ways in which sound and sonic procedures represent the Self and its crisis in the works of Salvatore Sciarrinio (b. 1947) and Helmut Lachenmann (b. 1935)—two composers who write music that involves extensive use of extended instrumental and vocal techniques. It also interrogates how the musical representation of the subject reflects the condition of human subjectivity as it was considered in contemporary intellectual discourse. This thesis begins with a conceptualization of the commonality in the musical poetics of the two composers and a theorization of a reception perspective that facilitates a fruitful interpretation of their music—based on the constellational and ecological approaches. The five chapters that follow analyse specific musical techniques in the light of some of their key aesthetic notions, exploring the condition of subjectivity through hermeneutic reading and philosophical reflection. Chapter 2 considers Sciarrinio’s mimetic gestures and the ideas of naturalism and organic music, arguing that Sciarrino’s music calls forth a post-humanist biotic aesthetics that at the same time embraces and negates classical organicism. Chapters 3 and 4 are devoted to two of Sciarrino’s operas. The former explores Luci mie traditrici through the idea of the semanticization of musical form, demonstrating that a Lacanian barred subject underlies the opera’s portrayal of troubled intersubjective relationships. The latter analyses the ecological significance of the multi-dimensional space-time in Lohengrin and revisits Sciarrino’s mimesis through the concept of becoming; it argues that the opera’s representation of a Proteus-like subjectivity enriches Sciarrino’s sonic mimesis. Chapter 5 deals with the relationship between nature and structure in Lachenmann’s musique concrète instrumentale, using the notion of aura to shed light on the way in which a self-reflexive listening subject comes into being in “…zwei Gefühle…”. Chapter 6 probes the entanglement of sound, image, and text in Lachenmann’s Das Mädchen mit den Schwefelhölzern through an investigation of the compositional procedure; the analysis demonstrates that the music’s articulation of a subjective voice is embedded in a sonic procedure that requires the deciphering work of an ideal listener.